2009
DOI: 10.1007/s00223-009-9317-8
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Ranelate Enhances Callus Strength More Than PTH 1-34 in an Osteoporotic Rat Model of Fracture Healing

Abstract: Treatment of an underlying disease is often initiated after the occurrence of an osteoporotic fracture. Our aim was to investigate whether teriparatide (PTH 1-34) and strontium ranelate affect fracture healing in ovariectomized (OVX) rats when provided for the first time after the occurrence of an osteoporotic fracture. We combined the model of an OVX rat with a closed diaphyseal fracture. Sixty Sprague Dawley rats were randomly assigned to four groups. Fracture healing in OVX rats after treatment with pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 43 publications
1
60
0
7
Order By: Relevance
“…SrRan seemed to represent a plausible solution in the setting of bone healing for our patient, since it could be speculated, based mainly on preclinical models (7)(8)(9)(10), that it would decrease further bone resorption locally by affecting the osteoclasts and possibly promote differentiation of prodromal cells of the osteoblastic lineage that would populate the bone lesions to osteoblasts. Indeed, in the setting of fracture healing, which is quite different than that of postmenopausal osteoporosis, data in animals suggest that SrRan may be beneficial as it is associated with improved bone microstructure, callus volume and biomechanical properties (21)(22)(23). Few case-reports in humans have also shown a positive effect of SrRan on fracture-healing either on atypical subtrochanteric fractures or fractures of the wrist or femur (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…SrRan seemed to represent a plausible solution in the setting of bone healing for our patient, since it could be speculated, based mainly on preclinical models (7)(8)(9)(10), that it would decrease further bone resorption locally by affecting the osteoclasts and possibly promote differentiation of prodromal cells of the osteoblastic lineage that would populate the bone lesions to osteoblasts. Indeed, in the setting of fracture healing, which is quite different than that of postmenopausal osteoporosis, data in animals suggest that SrRan may be beneficial as it is associated with improved bone microstructure, callus volume and biomechanical properties (21)(22)(23). Few case-reports in humans have also shown a positive effect of SrRan on fracture-healing either on atypical subtrochanteric fractures or fractures of the wrist or femur (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent evidence indicates that under conditions of impaired fracture healing, such as ovariectomy induced bone loss, SR exerts beneficial effects on the healing process, including increasing bone strength at the fracture site. 18 Although there are no animal studies concerning the effect of SR on stress fracture healing, a recent study reported a favourable outcome in two patients with AFF treated with SR. 5 Moreover, SR has some additional advantages such as post-hoc based evidence of hip fracture risk reduction in patients with high risk. 19 Thus, in patients with AFF treated in the past with TRP, having other contraindications to TRP, or even displaying significant future risk for hip fracture, SR treatment seems the most rational option.…”
Section: Discussionmentioning
confidence: 99%
“…Уникальное действие Бивалоса на костный метаболизм подтверждено у больных в ходе клинических исследований III фазы на основании измерения уровней костных марке-ров [18]. Оказалось, что использование Бивалоса приводит к значительному повышению уровня маркеров образования кости и уменьшает уровень маркеров костной резорбции начиная с 3-го месяца лечения.…”
Section: рассматривается возможность оптимизации лечения остеопороза unclassified